Evolving flood patterns in a Mediterranean region (1301–2012) and climatic factors – the case of Catalonia - A. Barrera-Escoda; M. C. Llasat (Hydrology and Earth System Sciences, 2015)
Data on flood occurrence and flood impacts for the last seven centuries in the northeastern Iberian Peninsula have been analysed in order to characterise long-term trends, anomalous periods and their relationship with different climatic factors such as precipitation, general circulation and solar activity. Catastrophic floods (those that produce complete or partial destruction of infrastructure close to the river, and major damages in the overflowed area, including some zones away from the channels) do not present a statistically significant trend, whereas extraordinary floods (the channel is overflowed and some punctual severe damages can be produced in the infrastructures placed in the rivercourse or near it, but usually damages are slight) have seen a significant rise, especially from 1850 on, and were responsible for the total increase in flooding in the region. This rise can be mainly attributed to small coastal catchments, which have experienced a marked increase in developed land and population, resulting in changes in land use and greater vulnerability. Changes in precipitation alone cannot explain the variation in flood patterns, although a certain increase was shown in late summer–early autumn, when extraordinary floods are most frequently recorded. The relationship between the North Atlantic circulation and floods is not as strong, due to the important role of mesoscale factors in heavy precipitation in the northwest of the Mediterranean region. However, it can explain the variance to some extent, mainly in relation to the catastrophic floods experienced during the autumn. Solar activity has some impact on changes in catastrophic floods, with cycles related to the quasi-biennial oscillation (QBO) and the Gleissberg solar cycle. In addition, anomalous periods of high flood frequency in autumn generally occurred during periods of increased solar activity. The physical influence of the latter in general circulation patterns, the high troposphere and the stratosphere, has been analysed in order to ...